Pengembangan Paket Pembelajaran Filsafat Pendidikan Islam Berbasis Critical Thinking - Ismail Ismail (Jurnal Teknologi Pendidikan)
The research aimed at developing packet on critical thinking based for learning and teaching in islamic education philoshophy. The materials designed by using the Dick and Carey models (2009). The model development steps begins by identify instructional goals, conduct instructional analysis, analyze learner and contexs, write performance objectives, develop assessment instrument, develop instructional strategy, develop and select instructional materials, design and conduct formative evaluation of instructional, revising, and design and conduct summative evaluation. The development process applied expext and empirical validation. Empirical validation conducted three field, one-to-one learner treatment 3 students, small group treatment which is cover 9 students, and large treatment 35 students. The research resulted that packet purposed could be effective on critical thinking learning and teaching in islamic education philosophy. Keywords: critical thinking, development, packet, philoshophy, islamic education.